2013
DOI: 10.1021/jo401779x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of β-Hydroxy-α-amino Phosphonic Acid Derivatives via Organocatalytic Direct Aldol Reaction of α-Isothiocyanato Phosphonates with Aldehydes

Abstract: α-Isothiocyanato phosphonates are first used as nucleophiles to react with aldehydes for the asymmetric synthesis of β-hydroxy-α-amino phosphonic acid derivatives. The process is catalyzed by a quinine-derived thiourea via cascade aldol/cyclization reaction, affording a wide range of protected β-hydroxy-α-amino phosphonates containing adjacent quaternary-tertiary stereocenters in up to 93% yield, up to 81% ee, and >99:1 dr. This work represents the first example of α-isothiocyanato phosphonates serving as nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Currently, the catalytic asymmetric phospha‐Michael, phospha‐Mannich [80.81,89,90,92] and phospha‐aldol reactions have demonstrated broad applications in the construction of enantioenriched phosphorus‐substituted heterocycles featuring a phosphorus‐containing stereocenter . Some reactions involving heterocycle ring formation based on phosphorus compounds bearing C( sp 3 )−P and C( sp 2 )−P bonds have also been employed to synthesize optically active carbon‐centered and phosphorus‐centered phosphorus‐substituted heterocycles. Identifying effective chiral catalysts and highly efficient catalytic asymmetric systems for the development of asymmetric synthesis of such compounds will no doubt become the future state of the art in this field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the catalytic asymmetric phospha‐Michael, phospha‐Mannich [80.81,89,90,92] and phospha‐aldol reactions have demonstrated broad applications in the construction of enantioenriched phosphorus‐substituted heterocycles featuring a phosphorus‐containing stereocenter . Some reactions involving heterocycle ring formation based on phosphorus compounds bearing C( sp 3 )−P and C( sp 2 )−P bonds have also been employed to synthesize optically active carbon‐centered and phosphorus‐centered phosphorus‐substituted heterocycles. Identifying effective chiral catalysts and highly efficient catalytic asymmetric systems for the development of asymmetric synthesis of such compounds will no doubt become the future state of the art in this field.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Yuan et al. employed α‐isothiocyanato phosphonates 345 for the enantioselective addition to aldehydes with bifunctional quinine‐derived thiourea 255 as catalyst via a cascade aldol/cyclization process, generating optically active β‐hydroxy‐α‐amino phosphonates 346 containing adjacent quaternary‐tertiary stereocenters (Scheme ) . Various aryl and alkyl aldehydes could be tolerated, giving the corresponding trans ‐adducts in up to 93% yield with up to >99:1 dr and 81% ee .…”
Section: Reactions Involving Heterocyclic Ring Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, for the first time, Yuan et al explored the reactivity of a-isothiocyanato phosphonates 267 for the diastereo-and enantioselective synthesis of b-hydroxy-a-aminophosphonic acid derivatives 266 (Scheme 89). [114] Quinine-thiourea C12 (20 mol %) catalyzed the addition of 267 to aldehydes 265 to afford derivatives 266 in moderate to good yields, enantio-and diastereoselectivities. In 2014, Wang et al reported the same reaction using quinine-squaramide C82, which catalyzed the production of 266 with excellent yield, enantio-and diastereoselectivities (Scheme 89).…”
Section: Càc Bond Formationmentioning
confidence: 99%
“…The poor nucleophilicity of anionic a-amino phosphonic acid equivalents results in a small equilibrium constant for their addition to electrophiles. We envisaged that the a-isothiocyanato phosphonates [14] would be perfect reactants because the anion generated in the addition step can subsequently be quenched by the isothiocyanate moiety, thus pushing the reaction forward (Scheme 1 b). Through the catalytic asymmetric Aldol and Mannich-type addition of aphosphonates, optically active b-hydroxy-a-amino (phosphoserine and phosphothreonine analogues) and a,b-diamino phosphonic acid derivatives can be obtained in an efficient manner.…”
mentioning
confidence: 99%